CYTOTOXICITY STUDY OF BIOMAGNETIC MEMBRANES WITH POTENTIAL APPLICATION IN GUIDED TISSUE REGENERATION - Andrei Mihai Gavrilovici; Mihai MC Fabricky; Marius Ciprian Manole; Dan Onisei; Cristina Vlad Daliborca; Ioan Bica; Meda-Lavinia Negruţiu (Romanian Journal of Oral Rehabilitation)
This study evaluates the cytotoxic effects of biomagnetic membranes on healthy human cells, with an emphasis on their suitability for use in guided tissue regeneration (GTR). The aim of this study was to evaluate the biocompatibility of impregnation products used in bioactive magnetic membranes on human fibroblasts. Fibroblasts were selected due to their essential role in the maintenance and remodeling of the extracellular matrix (ECM), where they contribute to the synthesis of critical structural components, particularly collagen fibers. These cells also influence cellular signaling pathways involved in tissue repair and regeneration. The biocompatibility of materials intended for use in GTR techniques is of paramount importance, as any cytotoxic effects could impair fibroblast function and compromise healing outcomes. Given the emerging interest in magnetically responsive biomaterials for controlled therapeutic applications, this study focused on determining whether the impregnated magnetizable membranes support fibroblast viability and could therefore serve as promising scaffolds for regenerative medicine.Using in vitro assays, the biocompatibility of the membranes was assessed, revealing minimal cytotoxicity and high potential for clinical application in regenerative medicine.